Polio-Like Illness Associated With Outbreak of Upper Respiratory Tract Infection in Children. (March 2016) - Crone, Megan; Tellier, Raymond; Wei, Xing-Chang; Kuhn, Susan; Vanderkooi, Otto G.; Kim, Jong; Mah, Jean K.; Mineyko, Aleksandra
Poliomyelitis is a historically devastating neurological complication of poliovirus infection. Poliovirus vaccines have decreased the incidence of poliomyelitis to 209 global cases in 2014, with new cases of acute flaccid myelitis primarily associated with nonpolio enteroviruses. Recently, during outbreaks of enterovirus D68 throughout North America and Europe, cases of acute flaccid myelitis have been reported, suggesting another nonpolio enterovirus associated with acute flaccid myelitis. The authors describe 3 patients diagnosed with acute flaccid myelitis during a province-wide outbreak of enterovirus D68 with the virus detected in 2 of the patients. Given the significant morbidity associated with acute flaccid myelitis and potential for nonpolio enterovirus to cause outbreaks, prompt identification and notification of public health authorities are warranted.